The effectiveness of moodle-based e-learning in enhancing digital literacy among village owned enterprises - Lia Pebriana Puspitasari; Sri Sumaryati; Sudiyanto Sudiyanto (SCHOULID: Indonesian Journal of School Counseling, 2023)
Amid the global spread of the Covid-19 pandemic, including in Indonesia, several activities have been forcibly halted to prevent wider transmission and avoid more severe impacts. This decision has affected the dynamics of education and training, prompting an increase in the use of E-Learning applications. E-Learning has become a crucial method in creating a supportive learning environment and enhancing learners' performance. The development and expansion of e-learning are made easy with Learning Management System (LMS) software, such as Moodle. This study utilizes the ADDIE research model (Analyze, Design, Develop, Implement, and Evaluate). The data analysis techniques employed include feasibility analysis and learning outcome analysis. Learning outcomes are compared using the paired sample t-test, assisted by SPSS software. Media expert assessments yielded an average score of 4.54 for the presentation aspect, indicating an ideal score of 90.85%, while the programming aspect scored 84% in terms of idealness. Material expert assessments, on the other hand, received an average score of 4.62 for the learning aspect, with an ideal score of 92.3%, and 4.57 for the material aspect, indicating an ideal score of 91.4%. The paired sample t-test analysis produced a Sig. (2-tailed) value of 0.000 with a significance level of 5%. This result indicates that the Sig. (2-tailed) value is less than α = 0.05. Therefore, it can be concluded that the hypothesis is accepted. Consequently, it can be inferred that the use of Moodle-based E-Learning products is effective in enhancing digital literacy among the managers of Bina Sejahtera Village Owned Enterprises.